UPAYA KEPALA SEKOLAH DALAM MENINGKATKAN PROFESIONALISME GURU DI SEKOLAH DASAR NEGERI 213 LUBUK BERINGIN - Sasmita; Subhanadri (Jurnal Muara Olahraga, 2024)
ABSTRACT Educating students to become good human beings cannot be separated from the role of teachers in carrying out their duties and responsibilities as teachers. Teachers are required to act as professional educators. The principal's role as a leader reflects the principal's responsibility to mobilize all existing resources in the school, so that a work ethic and high productivity are born in achieving goals. The leadership function is very important because apart from being a driving force, it also plays a role in controlling all teacher activities (in order to improve teaching professionalism). In educational institutions, a teacher's professionalism is very necessary to produce quality students. From the research results, it was found that the principal's efforts to improve teachers' pedagogical competence were by providing direct guidance and supervision to teachers related to the process of implementing learning in the classroom. The school principal's efforts to improve teacher personality competence by providing a good example for teachers. The school principal's efforts to increase social competence are by creating a sense of togetherness and family by improving communication between teachers. The school principal's efforts to improve teachers' professional competence, by providing guidance and involving teachers in training activities, seminars, workshops and KKG, to expand teachers' knowledge and gain new knowledge, so that they are able to apply it in the learning process at school. Key words: School Principal, Professional, Teacher